Political interest of religious ritual: The Sundanese Nyangku ritual in Indonesia - Santoso, Try Riduwan; Rahayu, Rizqi; Setiana, Adi Robith (IAS Journal of Localities, 2023)
Nyangku ritual is considered not only as an amplifier solidarity and friendship for Panjalu people, however it is also as an arena for political investment by political elites. This paper aims to analyze the political elites forms and factors of interest that involved in Nyangku ritual. This research is descriptive qualitative where the data obtained through observation, in-depth interviews and documentation. This study results indicate that there are three forms of political interest in rituals that appear to be carried out by political elite in Panjalu village from various activities such as; moral support shown by banners and posters and attendance, material support shown by providing financial assistance and action support by being directly involved in the process of Nyangku ritual event. The elite interests of community leaders and regional officials are a precedent for a shift in meaning marked by political activity in Nyangku ritual, which has implications for the ritual sacred values degradation. I argue that political interest in Nyangku ritual has shown a shift in meaning in society, namely from the sacred to the profane.